The COVID-19 Outbreak and Stock Market Return: Evidence from Indonesia - Nurcahyono Nurcahyono; Ayu Noviani Hanum; Fatmasari Sukesti (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2021)
This study investigates the impact of Coronavirus disease 2019 (COVID-19) outbreak on stock market returns in Indonesia stock exchange. Number of positive cases, mortality, recovery, and capital market data were collected for 136 days since the first case was announced in Indonesia (2 March 2020). Panel data regression was employed to test the research hypothesis. The results show that COVID-19 has a negative impact on Indonesian stock market returns. The growth of positive case and deaths decreased the market returns. Meanwhile, the increase of recovered cases is a positive signal for the capital market but it has not contributed to the rise of stock prices and market returns.